2009
DOI: 10.1677/joe-09-0046
|View full text |Cite
|
Sign up to set email alerts
|

Permissive action of protein kinase C-ζ in insulin-induced CD36- and GLUT4 translocation in cardiac myocytes

Abstract: Insulin stimulates cardiac long-chain fatty acid (LCFA) and glucose uptake via translocation of human homolog of rat fatty acid translocase (CD36) and GLUT4 respectively, from intracellular membrane compartments to the sarcolemma, a process dependent on the activation of phosphatidylinositol-3 kinase. To identify downstream kinases of insulin signaling involved in translocation of CD36 and GLUT4 in the heart, we tested i) which cardiac protein kinase C (PKC) isoforms (a, d, 3 or z) are activated by insulin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
(45 reference statements)
2
32
0
2
Order By: Relevance
“…In addition to their roles as mediators of ceramide-induced insulin resistance, atypical PKCs have been noted to relay critical signals for lipogenesis and lipid uptake (Luiken et al, 2009; Sajan et al, 2004; Sajan et al, 2009; Taniguchi et al, 2006). Consistent with this, aPKC expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their roles as mediators of ceramide-induced insulin resistance, atypical PKCs have been noted to relay critical signals for lipogenesis and lipid uptake (Luiken et al, 2009; Sajan et al, 2004; Sajan et al, 2009; Taniguchi et al, 2006). Consistent with this, aPKC expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PKCζ has also attracted attention for its role in lipid homeostasis, particularly as a mediator of SREBP-1c driven lipogenesis (Sajan et al, 2004; Sajan et al, 2009; Taniguchi et al, 2006). Moreover, PKCζ has also been previously noted to play a facilitative role in CD36 activation to promote lipid uptake into cardiomyocytes (Luiken et al, 2009). We show here that targeted manipulation of ceramide alters atypical PKC activation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, class II PI3Ks can be excluded because isoforms within this class are relatively resistant towards both inhibitors (108). Recent studies in L6 muscle cells and in primary cardiac myocytes using pharmacological inhibitors have found that downstream of PI3K, atypical PKC-, but not PKB/Akt, mediates the effects of insulin on fatty acid uptake (239) via translocation of CD36 (284). In contrast to L6 muscle cells, it does appear, however, that Akt-2 is required in mammalian muscle for insulin-induced fatty acid transport and for the translocation of selected fatty acid transporters.…”
Section: B) Insulin Signaling Pathways In Fatty Acid Transportermentioning
confidence: 99%
“…In PKCλ-knockout heart, insulin-stimulated glucose uptake is markedly reduced (54). The activity of PKCζ is required for insulin mediated GLUT4 translocation, although insulin does not further increase its activity in the heart (132). Therefore, PKCζ seems to play a permissive rather than a stimulatory role in insulin-mediated glucose uptake in cardiomyocytes (132).…”
Section: Glucose Transporter In the Heartmentioning
confidence: 99%